2007
DOI: 10.1007/s11581-007-0135-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on vacuum-evaporated CSZ thin films for thermal barrier applications

Abstract: Ceria-stabilized zirconia (CSZ) thin films have been developed over Ni-based alloy substrate by vacuum evaporation method using an electron beam. X-ray diffraction (XRD) analysis of the film heat treated at different temperatures reveals monoclinic phase stabilization. Transmission measurements of the films annealed at different temperatures, in the wavelength region 300-1,100 nm, indicate that the band gap energy of the films lies between 3.6 and 3.8 eV. Refractive index of the films was found to increase wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The low value of band gap may due to the non stoichiometric nature of the films. Moreover the band gap energy has been found to increase with the increase in concentration, which may be attributed to the increases in carrier density with increase in solute concentration [7]. …”
Section: Optical Characterizationmentioning
confidence: 96%
See 1 more Smart Citation
“…The low value of band gap may due to the non stoichiometric nature of the films. Moreover the band gap energy has been found to increase with the increase in concentration, which may be attributed to the increases in carrier density with increase in solute concentration [7]. …”
Section: Optical Characterizationmentioning
confidence: 96%
“…There has been great scientific concentration in Zirconia thin films due to their phase transitions. Pure Zirconia exhibits three polymorphs depending on temperature: monoclinic (m) stable up to1170˚ C, tetragonal (t) stable up to 1170-2370˚ C, and above it have cubic (c) phase until it melt at 2706˚ C [7]. The property of thin films strongly lies on the method of preparation and growth parameters.…”
Section: Introductionmentioning
confidence: 99%
“…turbine blades) with better efficiency. Yttria stabilized zirconia (YSZ) was usually selected as the thermal insulating coating material due to its low thermal conductivity, high thermal expansion coefficient and good corrosion resistance [1].In recent years, some investigators have reported that ceria stabilized zirconia (CSZ) coatings have not only high temperature stability, good corrosion resistance and high fracture toughness but also lower thermal conductivity and high thermal expansion coefficient than YSZ coatings [2][3][4]. Therefore, CSZ looks to be more promising as a new candidate material for the TBC application in more severe environment.…”
Section: Introductionmentioning
confidence: 99%